Dissimilar TLP bonding of X-45/Hastelloy X superalloys using BNi-2 filler metal: Microstructural evolution and mechanical behaviors - A. Yarmou shamsabadi; M. Farvizi; L. Nikzad; A. Malekan (Journal of Advanced Joining Processes, 2025)
This article explores the dissimilar joining of two commonly utilized superalloys, X-45 and Hastelloy X (HX), through the Transient Liquid Phase (TLP) bonding technique using BNi-2 filler metal. The TLP process was performed at 1050 °C for varying durations (5–60 min). Microstructural analyses indicated that longer holding times at 1050 °C alongside the diffusion of Melting Point Depressant (MPD) elements into the base materials led to the completion of isothermal solidification and the elimination of the eutectic structure from the Athermally Solidified Zone (ASZ). The MPD elements exhibited varying diffusion rates across the joint's two sides. Increased diffusion of elements on the Hastelloy X side resulted in denser and more widespread precipitates than on the opposite side of the joint, although this region produced harder precipitates. To analyze the connection between microstructure and mechanical properties, a combination of microhardness and shear testing was utilized. Shear tests revealed two distinct types of fractures for joints formed over different durations: one type occurred when isothermal solidification was not completed, resulting in a cleavage fracture with low shear strength and weak bonding due to brittle eutectic compounds in the ASZ, while the other happened when isothermal solidification was complete, showing ductile fracture from the Diffusion Affected Zone (DAZ) that had the highest hardness following ASZ removal. The increased density of precipitates and broader precipitation zone on the HX side promote crack propagation along the boride-rich grain boundaries in this region, ultimately leading to the final fracture.